Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyg.2021.734789
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Life, Satisfaction With Job, and the Level of Care Rationing Among Polish Nurses—A Cross-Sectional Study

Abstract: Background: Rationing of nursing care is a serious issue that has been widely discussed throughout recent years in many countries. The level of satisfaction with life and of satisfaction with job as the nurse-related factors may significantly affect the level of care rationing.Aim: To assess the rationing of nursing care among the Polish nurses and the impact of nurse-related variables, i.e., satisfaction with life and satisfaction with job on the level of nursing care rationing.Materials and Methods: A cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
(97 reference statements)
1
12
1
Order By: Relevance
“…The results obtained from the SWJS (SSP) questionnaire showed that the mean score was 11.71 points, indicating a level of job satisfaction between “dissatisfied” and “rather dissatisfied”. The obtained results did not correspond with other studies, in which nurses described their job satisfaction as neither satisfactory nor unsatisfactory [ 28 , 30 , 40 , 41 ]. However, there were significant discrepancies between the degrees of job satisfaction in the studies conducted in different countries.…”
Section: Discussioncontrasting
confidence: 99%
“…The results obtained from the SWJS (SSP) questionnaire showed that the mean score was 11.71 points, indicating a level of job satisfaction between “dissatisfied” and “rather dissatisfied”. The obtained results did not correspond with other studies, in which nurses described their job satisfaction as neither satisfactory nor unsatisfactory [ 28 , 30 , 40 , 41 ]. However, there were significant discrepancies between the degrees of job satisfaction in the studies conducted in different countries.…”
Section: Discussioncontrasting
confidence: 99%
“… 48 Healthcare worker satisfaction impacts productivity, quality, efficiency, and work engagement. 20 Health professionals need a greater commitment for a better job performance, since the care of patients in various stages of the disease, emotional implications, and shift work can be physically and mentally exhausting. Therefore, adequate working hours, efficient infrastructure, equipment, and materials, as well as an increase in personnel would improve the performance of the professional and decrease risk factors such as burnout syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The globalized world of the twenty-first century requires workers to be able to manage the challenges that globalization and technological progress entail (Maree and Di Fabio, 2018;Blustein et al, 2019;Guichard, 2022). Within this context, satisfaction with life has proven to be an important factor linked to job performance (Kołtuniuk et al, 2021), influencing quality, efficiency, and commitment to work (Lado et al, 2021). Therefore, the present research aimed at investigating the variables that may be associated with satisfaction with life in workers, by analyzing the role of resilience, career adaptability, self-efficacy, and years of education.…”
Section: Discussionmentioning
confidence: 99%